PROGRAM EVALUATION OF MUADALAH MUALLIMIN PESANTREN USING COUNTENANCE MODEL - Fawzul Arifin; Rizqi Nur Afifah; Syafa'at Ariful Huda (Jurnal Manajemen Pendidikan, 2026)
Pesantren have received state recognition, institutional strengthening, and equal rights in the implementation of educational activities through Law No. 18 of 2019 on Pesantren. Among the forms of pesantren officially recognized are pesantren muadalah operating under the salafiyah and muallimin systems; however, empirical evaluation studies on the implementation of the muadalah muallimin pesantren program remain limited. This study aims to assess the effectiveness of program implementation and to examine the application of an evaluation model in order to develop a systematic, contextual, and applicable evaluation framework that may serve as a reference for muadalah muallimin pesantren in Indonesia. This research employed a qualitative approach using a case study method and the Stake’s Countenance Evaluation Model. Data were collected through observation, interviews, and questionnaires. The evaluation criteria were based on government regulations concerning quality standards for pesantren education within muadalah muallimin educational units. The findings indicate that the implementation of the muadalah program achieved an excellent classification, attaining an A grade with a final score of 91. The component scores were as follows: curriculum 97.27, students 97.36, educators and educational staff 94.08, facilities and infrastructure 90.67, financing 100, institutional management 93.08, teaching and learning processes 91.27, and learning outcomes and graduates 61.75. This study contributes novel insights to the body of knowledge on program evaluation of muadalah muallimin pesantren.